Answer:
formula equation:
3 NaOH (aq) + H3PO4 (aq) → Na3PO4 (aq) + 3 H2O (l)
ionic equation:
H+(aq)+OH−(aq)→H2O(l)H+(aq)+OH−(aq)→H2O(l).
Step-by-step explanation:
1. Balance the equation
2. Write state symbols
3. Split the aqueous compounds to its ions. DO NOT SPLIT THE COMPOUNDS WHICH ARE NOT AQUEOUS
4. Cut the spectator ions from products and reactants side.
5. Write the remaining stuff as it is WITH state symbols..
3 NaOH (aq) + H3PO4 (aq) → Na3PO4 (aq) + 3 H2O (l)
3Na+(aq) 3OH-(aq) + 3H+(aq) PO4-3(aq)→ 3Na+(aq) PO4-3(aq) +3H2O(l)
(cut spectator ions and write the stuff that remains)
3H+(aq) + 3OH-(aq) → 3H2O(l)
BUT SINCE WE CAN SIMPLIFY THE EQUATION BY CUTTING ALL THE THREES IT BECOMES..
H+(aq) + OH-(aq) → H2O(l)
BTW IN EVERY NEUTRALIZATION REACTION IT HAS THE SAME IONIC EQUATION WHICH IS :
H+(aq) + OH-(aq) → H2O(l)